A New Paradigm for the Integrated Sustainability and Management of the Tehran Metropolis: Capital City Reorganization or Relocation - Mahmood Jomehpour (برنامه‌ریزی توسعه شهری و منطقه‌ای, 2018)
It seems that we are not in harmony with the changes of the Tehran metropolis as the capital city of Iran. We often encounter what Cowell and Owens call an implementation deficit. The pursuit of methods that are obviously ineffective and futile, or as Barbara Tuchman calls it, wooden-headedness, the inability to escape the dominant structural and institutional algebra. This structural and institutional algebra indicates a change in attitude and paradigm in this regard. Instead of focusing on Tehran's formation as a process and turning it into an issue, we deal with it as a project. While many factors turn Tehran into a problematic metropolis, it still continues to work. We need to do a reverse engineering of the process that has led to the creation of Tehran over two centuries. There is a need for fundamental change in the outlook towards customary processes and procedures, with a holistic, systemic, process-based, and far-sighted approach. A comprehensive, integrated, and systemic approach instead of a reductionist and abstract attitude; looking into the future rather than the present; a process-based approach instead of a project-based one; a program-centered look instead of a routine one. These are all solutions to Tehran's problem and the organization of the capital issue. The results of the analysis emphasize an integrated and systematic strategy of management in the framework of regional and transregional connections. They also focus on an ecologic attitude toward expanding the metropolis and creating balance between the natural and man-made environments.